A study on determinants of unemployment rate in Malaysia - Mohd Khalimi, Hani Wardati (2015)
This study aims to examine the effects of several macroeconomic variables on the unemployment rate in Malaysia. The research focuses on identifying the key determinants of unemployment by analyzing time-series data from 2007 to 2014 on a quarterly basis. The dependent variable is the unemployment rate, while the independent variables are Gross Domestic Product (GDP), inflation rate, interest rate, population, and exchange rate. A total of 30 secondary data observations for each variable were used in the study. The data was analyzed using Multiple Regression Analysis. The results indicate that both Gross Domestic Product and population have a significant positive relationship with the unemployment rate in Malaysia.